The Role of Epistemic Curiosity in Game-Based Learning: Distinguishing Skill Acquisition From Adaptation. (April 2020) - Huck, Jonathan T.; Day, Eric Anthony; Lin, Li; Jorgensen, Ashley G.; Westlin, Joseph; Hardy, Jay H.
Background: Videogames are emerging as increasingly popular tools for training complex skills, in part due to their potential for improving the transfer of learning to changing demands. One caveat is that training outcomes are primarily influenced by a learner's capability and willingness to engage in adaptive learning processes. The present study examined the role ofepistemic curiosity as a predisposition for seeking information and resolving gaps in knowledge. Method: Using a game-based learning environment with strong cognitive and perceptual-motor demands, we tested the effects of interest- and deprivation-type epistemic curiosity on performance duringskill acquisition andadaptation to unforeseen change. A task-change paradigm and piecewiselatent trajectory model disentangled the effects on performance trajectories corresponding to skill acquisition and adaptation. Results: Interest-type epistemic curiosity, but notdeprivation-type, was positively related to baseline performance, even after controlling for cognitive ability and videogame experience. Moreover, the positive effect of interest-type epistemic curiosity on post-change performance (i.e., adaptation) was fully mediated by pre-change performance. Discussion: These findings indicate that interest-type epistemic curiosity is particularly important in the earlier phases of learning, but explains little variability in adaptive performance beyond its direct influence on performance acquired prior to change. This research speaks to the roles of individual differences in cognition and motivation duringgame-based learning .